The KgA1c Paradox: Widening the spectrum - Sanjay Kalra; Suneet Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
The term KgA1c paradox is used to describe the unwanted rise in weight that occurs when HbA1c is controlled using conventional therapy. We highlight facets of pathophysiology, prevention, pharmacology, person centred care, and epidemiology, which correspond to the concept of KgA1c paradox. We suggest a novel index, KgA1c product [(BMI) x (HbA1c)], which can be used to evaluate efficacy of drugs, and assess metabolic control in persons with diabetes, Keywords: Diabesity, diabetes, HbA1c, metabolic syndrome, overweight, obesity